Bioactivation of plane and patterned PDMS thin films by wettability engineering - Scharin, Marina; Rommel, Mathias; Dirnecker, Tobias; Marhenke, Julius; Herrmann, B.; Rumler, Maximilian; Fader, R.; Frey, Lothar; Herrmann, Martin (BioNanoScience, 2014)
This study shows how surface properties of polydimethylsiloxane (PDMS) thin films, such as wettability and cellular adhesive behavior, can be influenced by surface modification and patterning, to improve the suitability of such modified PDMS for biomedical applications. For that purpose, different types of PDMS (i.e., soft (S-) and hard (H-) PDMS) and differently patterned surfaces were prepared by a commercially available tool which is originally used to produce patterned PDMS stamps for substrate conformal imprint lithography. To increase surface wettability and cellular adhesive behavior, PDMS surfaces were modified by O2, Ar/O2, Ar, and forming gas (N2/H2) plasma treatment. It is shown that, especially, plasma treatment using N2/H2 is a promising method to modify PDMS surfaces towards enhanced wettability. Such modified PDMS surfaces exhibit water contact angle values (WCA) of nearly 0° and demonstrate enhanced attachment of melanoma cells. Differences between as-prepared and plasma-treated S- and H-PDMS can be observed, where H-PDMS shows smaller WCA than S-PDMS. Even plasma-treated PDMS surfaces, however, exhibit only temporary hydrophilicity, due to hydrophobic recovery. To overcome this problem, plasma-treated PDMS films were stored in ethanol and water, where low and constant WCAs for several months could be achieved. Finally, the influence of surface topography of different patterned PDMS thin films on the adhesion behavior of melanoma cells was investigated. It can be concluded that chemical as well as structural modifications of PDMS enable to gradually control the adhesive properties of cells on their surfaces. This has a high technological impact since regulated and topologically stable adhesion and repulsion of cells by their scaffolds has high potency for in vitro as well as in vivo applications. © 2014 Springer Science+Business Media New York.
UnivIS-Import:2015-04-14:Pub.2014.tech.IE.LEB.bioact
Keywords: Biocompatibility; Cell adhesion; Hydrophilicity modification; PDMS; Surface patterning

Increasing flow rates in polydimethylsiloxane-based deterministic lateral displacement devices for sub-micrometer particle separation - Marhenke, Julius; Dirnecker, Tobias; Vogel, Nicolas; Rommel, Mathias (Microfluidics and Nanofluidics, 2022)
In this study, we show the design and manufacturing of microfluidic deterministic lateral displacement (DLD) devices for sub-micrometer particle separation. For that purpose, devices with pillar gaps of 4 µm and a periodicity of 50 were designed. After photolithographic manufacturing of SU-8 masters with different heights (15 and 30 µm) and vertical sidewalls for soft-lithographic replication with polydimethylsiloxane (PDMS) the influence of flow rate on the separation efficiency of 0.45 and 0.97 µm particles was investigated. The 15 µm devices were operated at 0.125 and 0.5 µl/min sample flow rate and the 30 µm devices at 0.5 and 2.0 µl/min, respectively. Excellent separation efficiencies were observed for both device heights at the lower sample flow rates, while separation efficiencies decreased at the respective higher sample flow rates. The decrease in separation efficiency was attributed to deformation of the soft PDMS pillars, which causes an increase in pillar gaps at the higher sample flow rates as shown by microscopy imaging. The advantage of the 30 µm devices over the 15 µm devices is clearly shown by the separation of 0.45 and 0.97 µm particles at 0.5 µl/min. Due to reduced hydrodynamic resistance in the 30 µm devices and thus less pillar deformation, the displacement efficiency of 0.97 µm particles was above 99% compared to 46–57% for the 15 µm devices. Our 30 µm devices demonstrated excellent separation at a tenfold higher sample flow rate with 0.5 µl/min compared to comparable PDMS-based devices operating in the same size regime.<br
Keywords: Deterministic lateral displacement (DLD); Polydimethylsiloxane (PDMS); Flow rate; Deformation

Stiffness influence on particle separation in polydimethylsiloxane-based deterministic lateral displacement devices - Marhenke, Julius; Dirnecker, Tobias; Vogel, Nicolas; Rommel, Mathias (Microfluidics and Nanofluidics, 2023)
Polydimethylsiloxane (PDMS) is a popular material to rapidly manufacture microfluidic deterministic lateral displacement (DLD) devices for particle separation. However, manufacturing and operation challenges are encountered with decreasing device dimensions required to separate submicron particles. The smaller dimensions, notably, cause high hydraulic resistance, resulting in significant pressure even at relatively low throughputs. This high pressure can lead to PDMS deformation, which, in turn, influences the device performance. These effects may often be overlooked in the design and operation of devices but provide a systematic source of error and inaccuracies. This study focuses in detail on these effects and investigates pillar deformation in detail. Subsequently, we discuss a potential solution to this deformation using thermal annealing to stiffen the PDMS. We evaluate the influence of stiffness on the separation performance at elevated sample flow rates with submicron particles (0.45 and 0.97 µm diameter). An excellent separation performance at high throughput is successfully maintained in stiffer PDMS-based DLD devices, while the conventional devices showed decreased separation performance. However, the increased propensity for delamination constrains the maximal applicable throughput in stiffer devices. PDMS deformation measurements and numerical simulations are combined to derive an iterative model for calculating pressure distribution and PDMS deformation. Finally, the observed separation characteristics and encountered throughput constraints are explained with the iterative model. The results in this study underline the importance of considering pressure-induced effects for PDMS-based DLD devices, provide a potential mitigation of this effect, and introduce an approach for estimating pressure-induced deformation.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Deformation; Deterministic lateral displacement (DLD); Polydimethylsiloxane (PDMS); Pressure; Stiffness